Экономический анализ альтернативной солнечной энергетики - Листровая, Елена Сергеевна; Бабакин, Дмитрий Николаевич (НТУ "ХПИ", 2016)
Предлагается внедрение солнечных батарей, как замену обычному, загрязняющему окружающую среду источнику энергии. В результате проведенного анализа изучались все стороны вопроса. В выводах указано, что современные ученые бьются над тем чтобы увеличить коэффициент полезного действия и тем самым снизить период окупаемости и саму стоимость оборудования в целом. Экономическая целесообразность установки солнечных батарей может занять от нескольких до десятков лет.

All known earth's resources are not unlimited and whether exhaust themselves sooner or later. Therefore it is necessary to think about the alternative energy form. One of these sources are solar panels convert the sun's energy in a person familiar electric current. They are perfectly mounted on the roofs of houses, on the walls, on the ground, they are silent, do not require special care for themselves, but today they are quite expensive, and thus prolong the economic payback. After analyzing, I note that at the moment, scientists from around the world working to increase the efficiency, and thus the efficiency of the battery and its feasibility. In developed countries, there is a public support program to switch to alternative solar energy, in consequence of which the government wants in the future to reduce the cost of energy production by conventional methods and improve the ecological situation. However, the battery is really environmentally friendly nuclear and thermal power stations, but the solar cells that make up the panel contain toxic substances such as lead, cadmium, gallium, arsenic. As well as the installation of solar station on the ground, occupies a large area and, accordingly, the land shadowing, which leads to a lack of sunlight and due to changes in the soil. The findings highlighted the economic feasibility, so to speak "in numbers" and as a consequence the result that not all countries today can afford this type of alternative energy.
Еconomic analysis of alternative solar energy
Keywords: внедрение солнечных батарей; экономическая целесообразность; эффективность; период окупаемости; перспектива; economic feasibility; analysis; efficiency; alternative energy; ecology